Mind Maps: Processed as Intuitively as Thought? Investigating Late Elementary Students’ Eye-Tracked Visual Behavior Patterns In-Depth - Merchie, Emmelien; Heirweg, Sofie; Van Keer, Hilde (Frontiers in Psychology, 2022)
In this study, 44 late elementary students’ visual behavior patterns when reading mind maps were investigated, more particularly, the intuitive processing nature of their visual characteristics, reading sequence and presentation mode (i.e., mind map before or after text). Eye-tracked data were investigated by means of static early attention and dynamic educational process mining (EPM) analysis and combined with learning performance and retrospective interview data. All students seem to struggle with the map’s radial structure during initial reading. Also, the picture’s position in the map diverts students from consecutively reading interconnected branches. EPM analyses revealed different reading patterns in proceeding reading behavior. Students receiving a text first, seem to grasp the radial structure slightly more and show higher information integration attempts. They also attained higher free recall and coherence scores. The study concludes with instructional design principles for urgently needed explicit visual literacy instruction in elementary grades.